Trait Anxiety sebagai Prediktor Fleksibilitas Kognitif pada Dewasa Awal - Dwi Ningrum, Laura; Lukman, Lukman; Fakhri, Nurfitriany (Universitas Negeri Makassar, 2025)
Cognitive flexibility ability is essential in navigating life, especially for early adults who face various developmental demands. One factor that influences cognitive flexibility is trait anxiety. This study aims to determine the effect of trait anxiety on cognitive flexibility in early adults in Makassar City. This study employed a quantitative method with a simple regression research design. The research subjects consisted of early adults aged 18 to 25 years, totaling 232 respondents. The sampling technique used convenience sampling. The research instruments used were the State-Trait Anxiety Inventory (STAI) to measure trait anxiety and the Cognitive Flexibility Scale (CFS) to measure cognitive flexibility. Data analysis technique used simple regression analysis with SPSS version 26. The results showed that there was a significant negative effect of trait anxiety on cognitive flexibility in early adults, meaning that the higher the trait anxiety, the lower the cognitive flexibility. Trait anxiety contributed to cognitive flexibility in early adults, while the rest was influenced by other factors. The majority of subjects had trait anxiety in the high category and cognitive flexibility in the moderate category. The implication of this study is the importance for early adult individuals to develop cognitive flexibility abilities in responding to difficult situations they face so that they can optimize self-development in carrying out their life roles and responsibilities.